Obtenção e caracterização de revestimento de ZN-Mn em meio de sulfato - Ferreira Júnior, José Milton (2008)
The development of alloys that are resistant to corrosion and good wear resistance led to several studies on the electrodeposition field. With the intention of carry out alloys with good mechanic properties, associated to a high corrosion resistance, Zn-Mn alloys have been frequently studied in the last years, once they offer better anticorrosive characteristics when compared to metallic zinc films, usually used in the conventional industry. This work aimed obtain and characterize Zn-Mn alloy electrodeposited on platinum electrode and metallic cooper from solutions composed by sulfate salts from the metals previously mentioned. Zn-Mn alloys were studied by using of cyclic and linear voltammetry, and also chronoamperommetry, in which all samples were obtained in bath without agitation, room temperature, 25º C, on different current densities. The physical and morphological structure of the alloys that have been obtained were analyzed by using technique such as scanning electronic microscopy (SEM) and X-ray dispersive energy (XDE), varying parameters such as: current density applied, pH, deposition temperature and reagents concentration in the bath. In order to analyze the chemical structure of the species formed on the alloy mentioned, a x-ray diffraction (XRD) technique was used with the samples obtained in cooper electrode. From the results obtained through voltammetric analyses, it is possible to determine the potential of reduction and oxidation of Zn-Mn alloy, which occurred separately to zinc and manganese. It was possible to observe that the manganese in the alloy appears as the oxide and the zinc as an isolated metal. Through XRD analysis, it was possible to determine the phases in which the Zn-Mn species appears in the alloy, and also isolated zinc and manganese. The best results were obtained when was applied 10mA.cm-2 current density; pH 6,0; room temperature and 1:1 proportion of zinc and manganese in the electrolytic bath.